Unmet Need: Evaluating Pell as a Lever for Equitable Dual Enrollment Participation and Outcomes. (December 2022) - Bettinger, Eric P.; Lu, Amanda; Matheny, Kaylee T.; Kienzl, Gregory S.
Dual enrollment is an increasingly popular avenue for high school students to earn college credit. However, low-income students are underrepresented among dual enrollment participants. In this study, we use a difference-in-differences design to evaluate a unique federal pilot program that allowed high school students to access Pell Grants to fund their dual enrollment. Generally, we find a negative effect of the pilot program on dual enrollment participation, with no effect on subsequent college attendance. Our qualitative analysis suggests this initiative did not sufficiently meet students' specific needs, required strong partnerships with high schools to ensure high school counselors informed students about the program, and involved substantial financial and administrative burden for participating institutions.